Апотропеическая сила воды в армянских верованиях - Исраелян, Астхик (Институт языкознания РАН)
Various properties of water are manifested in folk tales, fables, customs etc. Water in the form of rain and river symbolizes amelioration, reproduction, fruitfulness, fertility. The idea of apotropaic power of water is deeply rooted in folk beliefs. The cult of water is related to cults of fire, light, thunder, oxen, stones and trees. It is said to purify both body and soul. Water plays an important and mandatory role in rites of healing, fortune telling, exorcism and inducing rain. It also drives out evil spirits and defeats “evil eye” (jinx) in everyday life and in the festive times of celebrating New Year’s, Christmas, Ascension, Transfiguration and other holidays.
Keywords: Этнография; Фольклор